Surface Waves on Self-Complementary Metasurfaces: All-Frequency Hyperbolicity, Extreme Canalization, and TE-TM Polarization Degeneracy - Oleh Yermakov (American Physical Society, 2021)
Self-complementary metasurfaces have gained significant attention due to their unique frequency-independent transmission and reflection properties and the possibility of the polarization transformation of plane waves. In this paper, we focus on the near-field spectrum to investigate, both theoretically and experimentally, the properties of surface waves supported by anisotropic self-complementary metasurfaces. We show that as a consequence of the electromagnetic Babinet’s duality, such a structure is hyperbolic for any frequency. We demonstrate the possibility of switching the canalization direction of surface waves with ultimately flat phase fronts for 90° by a very small frequency shift, paving the way to the extreme tunability and surface-wave routing. We reveal the polarization degree of freedom inherent to plane waves by demonstrating the all-frequency TE-TM polarization degeneracy of the surface waves along two principal directions. The results obtained open a plethora of opportunities for practical applications, including flat polarization devices, optical data-processing systems, sensing, holography and antennas.